Daprodustat Accelerates High Phosphate-Induced Calcification Through the Activation of HIF-1 Signaling - Tóth, Andrea; Csiki, Dávid Máté; Nagy, Béla; Balogh, Enikő; Lente, Gréta; Ababneh, Haneen; Szöőr, Árpád; Jeney, Viktória (Frontiers in Pharmacology, 2022)
Aims: Chronic kidney disease (CKD) is frequently associated with other chronic diseases including anemia. Daprodustat (DPD) is a prolyl hydroxylase inhibitor, a member of a family of those new generation drugs that increases erythropoiesis via activation of the hypoxia-inducible factor 1 (HIF-1) pathway. Previous works showed that HIF-1 activation is ultimately linked to acceleration of vascular calcification. We aimed to investigate the effect of DPD on high phosphate-induced calcification. Methods and results: We investigated the effect of DPD on calcification in primary human aortic vascular smooth muscle cells (VSMCs), in mouse aorta rings, and an adenine and high phosphate-induced CKD murine model. DPD stabilized HIF-1α and HIF-2α and activated the HIF-1 pathway in VSMCs. Treatment with DPD increased phosphate-induced calcification in cultured VSMCs and murine aorta rings. Oral administration of DPD to adenine and high phosphate-induced CKD mice corrected anemia but increased aortic calcification as assessed by osteosense staining. Inhibition of the transcriptional activity of HIF-1 by chetomin or silencing of HIF-1α attenuated the effect of DPD on VSMCs calcification. Conclusion: Clinical studies with long follow-up period are needed to evaluate the possible risk of sustained activation of HIF-1 by DPD in accelerating medial calcification in CKD patients with hyperphosphatemia.